2022
DOI: 10.2147/jir.s354878
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Hepatic Steatosis, Oxidative Stress, Inflammation, Ballooning and Insulin Resistance After Therapy with Safranal in NAFLD Animal Model: A New Approach

Abstract: Introduction Non-alcoholic fatty liver disease (NAFLD) is intimately linked to hepatic steatosis, inflammation, insulin resistance (IR), oxidative stress (OS), and ballooning. A high fat diet (HFD) is considered a major etiological factor that primarily covers the numerous features of NAFLD. Methods The present study aimed to evaluate the protective effect of safranal on hepatic steatosis, OS, liver index, IR index, liver function enzymes, plasma lipids, TNF-α, malondia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…In this study, the LNQ diet caused higher protein damage compared to C with significant differences only in the liver, even when the ROS did not show any significant differences in this tissue (probably due to a low-sensitivity technique). Sabir et al [ 40 ] found elevated AOPP levels in the liver of male Sprague–Dawley rats fed a high-fat diet, correlated with an increase in the reactive nitrogen species. Hence, the protein damage observed in this study could also be produced by other mechanisms apart from the ROS.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the LNQ diet caused higher protein damage compared to C with significant differences only in the liver, even when the ROS did not show any significant differences in this tissue (probably due to a low-sensitivity technique). Sabir et al [ 40 ] found elevated AOPP levels in the liver of male Sprague–Dawley rats fed a high-fat diet, correlated with an increase in the reactive nitrogen species. Hence, the protein damage observed in this study could also be produced by other mechanisms apart from the ROS.…”
Section: Discussionmentioning
confidence: 99%
“…Although MAFLD is a new term adopted in the last few years, previous animal studies on fatty liver disease, such as those mentioned in this study, have extensively unraveled the pathogenesis of MAFLD rather than NAFLD. These studies mostly used diet-induced fatty liver disease models, such as high-fat diet-induced fatty liver model and high-fat and high-sugar diet-induced fatty liver model, which can simultaneously induce liver steatosis, obesity, dyslipidemia, and other components of metabolic syndrome, suggesting that despite their titles, they mostly studied the pathogenesis and treatment of MAFLD instead of NAFLD [180][181][182]. Furthermore, recent studies on the pathogenesis and treatment of MAFLD have employed the same methods to induce the disease [183][184][185].…”
Section: Metabolic Dysfunction-associated Fatty Liver Disease (Mafld)mentioning
confidence: 99%
“…There is a crosstalk between parenchymal and non-parenchymal cells, where different mediators are released to activate multiple signaling pathways viciously, all of which directly or indirectly trigger HSC activation and fibrosis (Fangming Yang et al, 2021). The molecular pathways are illustrated in Figure 1 (Mashek, 2021;Sabir, Irfan, Ullah, et al, 2022). Injury-induced inflammation drives the recruitment of macrophages and KCs during fibrogen- HSC proliferation, and inhibit their apoptosis (Foglia et al, 2019;Tang et al, 2017).…”
Section: Cells Involved In Hepatic Fibrogenesis and Molecular Pathwaysmentioning
confidence: 99%